Enhancing Islamic Educational Quality through Output-Based Quality Assurance: A Literature Review Perspective - Sulfiani, Sulfiani; Nora Saiva Jannana; Sedya Sentosa (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This research undertakes a comprehensive literature review to analyze output-based quality assurance in Islamic educational institutions. The study systematically reviews scholarly articles published between 2019 and 2023, focusing on quality assurance and educational institution outputs. The findings highlight the pivotal roles of vision and mission alignment, strategic program implementation, robust facilities, and the cultivation of academically and competitively adept graduates. Key outcomes from the review include the importance of effective communication in achieving Islamic institutional goals, the significance of academic and non-academic flagship programs, and the criticality of a strong teaching and learning process. The study also reveals the efficacy of integrating strategic planning, stakeholder engagement, and a balance of academic excellence and character development in enhancing educational quality. Despite its comprehensive nature, the research acknowledges limitations in its scope, primarily its reliance on existing literature, which may not encompass all possible educational contexts. Future research should explore diverse educational settings further and assess the long-term impacts of quality assurance strategies on student outcomes and Islamic institutional reputation. This study significantly contributes to the discourse on educational quality assurance, advocating for comprehensive, adaptable, and inclusive strategies in response to the evolving demands of the educational landscape.